Various Novel and Emerging Technologies in Endoscopic Bariatric and Metabolic Treatments - Hee Kyong Na; Diogo Turiani Hourneaux De Moura (Korean Society of Gastrointestinal Endoscopy, 2021)
Obesity, along with its comorbidities, has become a significant public health concern worldwide. Bariatric surgery is considered the most effective treatment modality; however, only 2% of patients with obesity undergo bariatric surgery. Endoscopic bariatric and metabolic therapies (EBMTs) are emerging alternatives to traditional bariatric surgery for patients who are not eligible for or do not prefer surgical treatment. EBMTs are generally categorized as space-occupying, gastric restrictive, aspiration, and small bowel therapies. We aimed to review various non-balloon and non-gastroplasty devices with available clinical data and discuss the possible mechanisms of action, efficacy, and safety profile of these EMBTs.